2014
DOI: 10.1371/journal.pone.0084402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combining 2 Weeks of Passive Sensory Stimulation with Active Hand Motor Training in Healthy Adults

Abstract: The gold standard to acquire motor skills is through intensive training and practicing. Recent studies have demonstrated that behavioral gains can also be acquired by mere exposure to repetitive sensory stimulation to drive the plasticity processes. Single application of repetitive electric stimulation (rES) of the fingers has been shown to improve tactile perception in young adults as well as sensorimotor performance in healthy elderly individuals. The combination of repetitive motor training with a preceding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…In contrast, perceptual training, such as passive limb movement, directly enhances motor learning161718. In addition, exposure to extensive tactile stimulation enhances not only tactile acuity but also manual motor dexterity1920. These empirical findings support the notion that perceptual and motor learning generally occur together.…”
mentioning
confidence: 62%
“…In contrast, perceptual training, such as passive limb movement, directly enhances motor learning161718. In addition, exposure to extensive tactile stimulation enhances not only tactile acuity but also manual motor dexterity1920. These empirical findings support the notion that perceptual and motor learning generally occur together.…”
mentioning
confidence: 62%
“…This area of the brain particularly comes into play when students consider visual or spatial representations of quantity, such as a number line [2]. A number line representation of number quantity has been shown in cognitive studies to be particularly important for develop better representations of their fingers, which leads to higher mathematics achievement [10,11]. Researchers found that when 6 year old's improved the quality of their finger representation they improved in arithmetic knowledge, particularly subitizing1, counting and number ordering.…”
Section: What Does the Brain Science Say?mentioning
confidence: 99%
“…The cross-modality plasticity theory suggested that somatosensory stimuli could evoke neural responses to promote learning of new motor skills (Sanes and Donoghue, 2000;Nasir et al, 2013;Ladda et al, 2014) and performing motor tasks more accurately (Pearson, 2000). The integration of the orofacial sensory and motor system has been suggested to be critical for motor learning and motor control for sucking, swallowing, and producing speech sounds (Barlow and Bradford, 1996;Barlow, 1998;Sessle et al, 2005Sessle et al, , 2007Barlow and Estep, 2006;Barlow and Stumm, 2010;Smith, 2016).…”
Section: Introductionmentioning
confidence: 99%